THE USE OF COMMERCIAL BANKS IN AQABA FOR ACCOUNTING INFORMATION IN INVESTMENT DECISIONS IN THE TOURIST COMPANIES - Mohammad Nayef ALsarayreh; Fairouz Mosleh Mohammed Al Dhmour; Khalaf Suhail Bqain; Muneer Mohamad Falah Jaradat (European Scientific Journal, ESJ, 2012)
This study came to demonstrate the extent to which Aqaba banks depend on accounting information in investing decisions in tourist companies, a questionnaire was designed for this purpose and distributed to the banks and After analyzing the collected data some conclusions were reached the most important on of them is that, banks use accounting information in tourism companies they want to invest in them, with the exception of some things that they lacked, such as not using financial reports to predict the future of these companies, and not studying the notes, disclosures ,subsequent events, and the policies and accounting methods used in the preparation of the financial statements of these companies, And not studying the companies keeping up with the developments in the field of its activity. The most recommended by the study is that, banks should use the financial reports of the tourism company they want to invest in it in the best way, study notes, disclosures, subsequent events for the financial statements, and the policies and accounting methods used in the preparation of the financial statements and study the company's ability to repay its investment in short-term obligations. And examine the companies keeping up with the developments in the field of its activity.